Inhibitory to non-inhibitory evolution of the ζ subunit of the F1FO-ATPase of Paracoccus denitrificans and α-proteobacteria as related to mitochondrial endosymbiosis - Mendoza-Hoffmann, Francisco; Yang, Lingyun; Buratto, Damiano; Brito-Sánchez, Jorge; Garduño-Javier, Gilberto; Salinas-López, Emiliano; Uribe-Álvarez, Cristina; Ortega, Raquel; Sotelo-Serrano, Oliver; Cevallos, Miguel Ángel; Ramírez-Silva, Leticia; Uribe-Carvajal, Salvador; et al. (Frontiers in Molecular Biosciences, 2023)
The ζ subunit is a strong inhibitor of the F1FO-ATPase of Paracoccus denitrificans (PdF1FO-ATPase) and related α-proteobacteria different from the other two cannonical inhibitors of bacterial (ε) and mitocondrial (IF1) F1FO-ATPases. ζ mimicks mitochondrial IF1 in its inhibitory N-terminus, blocking the PdF1FO-ATPase activity as unidirectional pawl-ratchet, and allowing the PdF1FO-ATP synthase turnover. ζ is essential for the respiratory growth of P. denitrificans as we showed by a Δζ knockout. Given the key role of ζ in the physiology of P. denitrficans, here we assessed the evolution of ζ across the α-proteobacteria class. Through bioinformatic, biochemical, molecular biology, functional, and structural analyses of other ζ subunits, we confirmed the conservation of the inhibitory N-terminus of ζ and its divergence towards its C-terminus. We reconstituted homologously or heterologously the recombinant ζ subunits from several α-proteobacteria into the respective F-ATPases, including free-living photosynthetic, facultative symbiont, and intracellular facultative or obligate parasitic α-proteobacteria. The results show that ζ evolved preserving its inhibitory function in free-living α-proteobacteria exposed to wide environmental changes that could compromise the cellular ATP pools. However, the ζ inhibitory function was diminished or lost in some symbiotic α-proteobacteria where ζ is non-essential given the possible exchange of nutrients and/or ATP from hosts. Accordingly, the ζ gene is absent in some strictly parasitic pathogenic Rickettsiales, which may obtain ATP from the parasitized hosts. We also resolved the NMR structure of the ζ subunit of Sinorhizobium meliloti (Sm-ζ), and compared it with its structure modeled in AlphaFold. We found a transition from a compact ordered non-inhibitory conformation, into an extended α-helical inhibitory N-terminus conformation, thus explaining why the Sm-ζ is unable to exert homologous inhibition, but it still inhibits heterologously the PdF1FO-ATPase. Together with the loss of the inhibitory function of α-proteobacterial ε, the data confirms that the main inhibitory function of the α-proteobacterial F1FO-ATPase was transferred from ε to ζ, and that ζ, ε, and IF1 evolved by convergent evolution. Some key evolutive implications on the endosymbiotic origin of mitochondria, as most likely derived from α-proteobacteria are also discussed.